Tradition-Based Islamic Renewal: An Analysis of Nahdlatul Ulama's Thought in the Context of Religious Moderation - Nurul Fajriyah; Kholilur Rahman; Zainuddin Syarif (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study was motivated by the need to strengthen religious moderation amid the challenges of globalization, intolerance, and radicalism that threaten national harmony. Nahdlatul Ulama (NU), as the largest Islamic organization in Indonesia, has a unique tradition and contributes to strengthening national values. The purpose of this study is to analyze how the three main traditions of NU, namely religious practices (tahlilan, maulid, istighotsah), Islamic boarding schools and Bahtsul Masail, as well as the discourse of Islam Nusantara, play a role in building Islamic moderation in Indonesia. The research method used is qualitative-descriptive with a literature study approach that examines scientific literature, including journal articles, books, and relevant official documents. The results of the study show that NU practices serve to maintain social harmony, Islamic boarding schools and Bahtsul Masail develop adaptive scientific traditions, and Islam Nusantara provides a contextual framework of thought. In conclusion, NU traditions are not only historical legacies, but also actual instruments in maintaining national unity and responding to contemporary religious issues.